The dialogical challenge of leadership development - Koonce, Rob; Loon, E. J. P. van; Gergen, Kenneth J. (Contemporary perspectives on leadership development., 2019)
"In the foreword to The Dialogical Challenge of Leadership Development, eminent scholar Ken Gergen shrewdly points to dialogue as an optimal tool for organizational communication in the 21st century. Gergen's comment serves as a quintessential backdrop of the book you are about to read. Dialogical practice is no longer a distant option for organizational leaders to passively consider. Instead, it has become an indispensable tool for leaders who understand the critical significance of relational influence and sustainability for navigating today's increasingly complex and wicked organizational and societal challenges. Thanks to the wide-ranging talent and varied perspectives of leading scholars and seasoned practitioners from around the globe who graciously contributed to this volume, The Dialogical Challenge of Leadership Development offers compelling evidence that--whether they arise from Brazilian favelas or the world's largest corporate boardrooms--the challenges which leaders face on a daily basis can be effectively addressed through dialogical practice"--